Más allá de la recaudación: los límites de la extrafiscalidad (Sección Abierta) - Celi Masache, Maryuri Elizabeth (2025)
The study of extrafiscal taxes as instruments of public policy requires considering the theory of the Policy Cycle, which posits that public policies go through a series of stages: problem identification, policy formulation, adoption, implementation, evaluation, and termination. Therefore, public policy instruments are not permanent over time. This paper raises the discussion on the development of limits to extrafiscality, linked to its nature as a public policy instrument, to ensure a coherent exercise of taxing power. It also explores the possibility of enhancing transparency in the process of its creation, management, and outcomes. The proposed limits include material competence, proportionality, a structure linked to the extrafiscal objective, prohibition of punitive measures, avoidance of hindering behaviors, legislative justification, legitimacy control, coherence of the tax structure, and the evaluation and analysis of results. The article analyzes these limits and their importance in creating taxes that respond to extrafiscal objectives, moving beyond the logic of transparency based solely on revenue collection. Transparency plays a fundamental role in revealing the real motives behind their creation and in evaluating the results of their enforcement and application.